MicroRNA-21 and microRNA-29a modulate the expression of collagen in dermal fibroblasts of patients with systemic sclerosis - Saeideh Jafarinejad-Farsangi; Farhad Gharibdoost; Ali Farazmand; Hoda Kavosi; Ahmadreza Jamshidi; Elham Karimizadeh; Farshid Noorbakhsh; Mahdi Mahmoudi (Taylor & Francis Group, 2019)
MicroRNAs (miRNAs) are well-known candidates for modulating the dysregulated signaling pathways during fibrosis. In this study, we investigated the expression pattern of 16 miRNAs, which have previously been confirmed or predicted to target genes involved in extracellular matrix (ECM) homeostasis. Primary culture of dermal fibroblasts was obtained from skin biopsies of diffused cutaneous SSc (dcSSc) patients and healthy controls. Expression of let-7a, miR-1, miR-15a, miR-17, miR-19a, miR-20a, miR-21, miR-27b, miR-26a, miR-29a, miR-29b, miR29c, miR-141, miR-125a-5p, miR-193a-3p, and miR-200a were quantified by Real-time PCR. Functional analysis of microRNAs was performed using synthetic oligonucleotides. To further confirm the pro- or anti-fibrotic effects of miRNAs, normal fibroblasts were treated with 10 ng/mL of transforming growth factor (TGF)-β to generate an in vitro model of dermal fibrosis. miR-21 and miR-29a were upregulated and downregulated, respectively, in both dcSSc and TGF-β-treated fibroblasts. We observed that restoration of miR-29a expression or blockade of miR-21 function negatively affected collagen production. COL1A1 expression in SSc fibroblasts is more sensitive to changes of miR-29a and miR-21 expression in compare to normal fibroblasts. miR-29a alone was effective to decrease TGF-β-induced collagen production in dermal fibroblasts. miR-21 and TGF-β had synergistic effects on induction of collagen production. However, neither miR-21 nor miR-29a affected alpha smooth muscle actin (α-SMA) expression in the presence or absence of TGF-β in dermal fibroblasts. miR-21 and miR-29a as pro- and anti-fibrotic miRNAs modulate collagen production in an opposing manner. Focusing on miR-21 and miR-29s as therapeutic targets would be effective in patients with SSc or other fibrotic diseases which show aberrant expression of collagen expression.